2020
DOI: 10.1109/jiot.2019.2947419
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Information Freshness in Computing-Enabled IoT Networks

Abstract: Internet of Things (IoT) has emerged as one of the key features of the next generation wireless networks, where timely delivery of status update packets is essential for many realtime IoT applications. To provide users with context-aware services and lighten the transmission burden, the raw data usually needs to be preprocessed before being transmitted to the destination. However, the effect of computing on the overall information freshness is not well understood. In this work, we first develop an analytical f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 54 publications
1
58
0
Order By: Relevance
“…This helps to construct the decision making on the image conversion. The image conversion is works based on the sensing image by a rear image sensor [63].…”
Section: B Semi-automatic "Division B" Results Image Eventmentioning
confidence: 99%
“…This helps to construct the decision making on the image conversion. The image conversion is works based on the sensing image by a rear image sensor [63].…”
Section: B Semi-automatic "Division B" Results Image Eventmentioning
confidence: 99%
“…The AoI jointly characterizes the packet delay and the packet intergeneration time, which distinguishes AoI from conventional metrics, such as delay and throughput. Such a superiority of AoI for evaluating the information freshness in various wireless networks has been demonstrated in recent studies [5]- [8] by resorting to queueing theory.…”
Section: Introductionmentioning
confidence: 91%
“…[50] considered AoI in a general multi-hop network where the update packets do not necessarily arrive to the gateway node in the order of their generation times. Xu et al [51] calculated and optimized the average PAoI and found the optimal updating frequency in IoT network. The problem of optimizing link scheduling decisions to minimize the expected weighted sum AoI of the clients in the network was researched [52].…”
Section: Real-time Guaranteementioning
confidence: 99%